Relationship Between Sleep Quality and Spiritual Well-Being/Religious Activities in Muslim Women with Breast Cancer - Khoramirad, Ashraf (Journal of religion and health, 2015)
For determining relationship between quality of sleep and spiritual well-being/religious activities in Muslim women with breast cancer (WBC), we conducted a cross-sectional study on 80 WBC who presented at all chemotherapy clinics in Qom, Iran, in 2012. We used Pittsburgh Sleep Quality Index (PSQI), spiritual well-being scale (SWBS), and religious activities (RA) questionnaire. Global PSQI score and its seven components score were not significantly correlated with total score of SWBS and its two subscales. Global PSQI score was not significantly correlated with total score of RA questionnaire (P = 0.278), but its “sleep latency” (r = 0.235, P = 0.044) and “use of sleep medications” (r = 0.237, P = 0.040) components were significantly correlated with total score of RA. Global PSQI was significantly correlated with “I don’t get much personal strength and support from my God,” “I believe there is some real purpose for my life” questions in SWBS, and “Attendance in mosque or religious places” subscale of RA.